Motor uncoordination and neuropathology in a transgenic mouse model of Machado-Joseph disease lacking intranuclear inclusions and ataxin-3 cleavage products - Fernandes, Anabela Silva (2010)
Machado-Joseph disease (MJD) is a late-onset neurodegenerative disorder caused by a polyglutamine (polyQ) expansion in the ataxin-3 protein. We generated two transgenic mouse lineages expressing the expanded human ataxin-3 under the control of the CMV promoter: CMVMJD83 and CMVMJD94, carrying Q83 and Q94 stretches, respectively. Behavioral analysis revealed that the CMVMJD94 transgenic mice developed motor uncoordination, intergenerational instability of the CAG repeat and a tissue-specific increase in the somatic mosaicism of the repeat with aging. Histopathological analysis of MJD mice at early and late stages of the disease revealed neuronal atrophy and astrogliosis in several brain regions; however, we found no signs of microglial activation or neuroinflammatory response prior to the appearance of an overt phenotype. In our model, the appearance of MJD-like symptoms was also not associated with the presence of ataxin-3 cleavage products or intranuclear aggregates. We propose the transgenic CMVMJD94 mice as a useful model to study the early stages in the pathogenesis of MJD and to explore the molecular mechanisms involved in CAG repeat instability.